Assessment of Minimum Important Difference and Substantial Clinical Benefit with the Vascular Quality of Life Questionnaire-6 when Evaluating Revascularisation Procedures in Peripheral Arterial Disease. (September 2017) - Nordanstig, J.; Pettersson, M.; Morgan, M.; Falkenberg, M.; Kumlien, C.
Abstract : Objectives: Patient reported outcomes are increasingly used to assess outcomes after peripheral arterial disease (PAD) interventions. VascuQoL-6 (VQ-6) is a PAD specific health-related quality of life (HRQoL) instrument for routine clinical practice and clinical research. This study assessed the minimum important difference for the VQ-6 and determined thresholds for the minimum important difference and substantial clinical benefit following PAD revascularisation. Materials and methods: This was a population-based observational cohort study. VQ-6 data from the Swedvasc Registry (January 2014 to September 2016) was analysed for revascularised PAD patients. The minimum important difference was determined using a combination of a distribution based and an anchor-based method, while receiver operating characteristic curve analysis (ROC) was used to determine optimal thresholds for a substantial clinical benefit following revascularisation. Results: A total of 3194 revascularised PAD patients with complete VQ-6 baseline recordings (intermittent claudication (IC) n = 1622 and critical limb ischaemia (CLI) n = 1572) were studied, of which 2996 had complete VQ-6 recordings 30 days and 1092 a year after the vascular intervention. The minimum important difference 1 year after revascularisation for IC patients ranged from 1.7 to 2.2 scale steps, depending on the method of analysis. Among CLI patients, the minimum important difference after 1 year was 1.9 scale steps. ROC analyses demonstrated that the VQ-6 discriminative properties for a substantial clinical benefit was excellent for IC patients (area under curve (AUC) 0.87, sensitivity 0.81, specificity 0.76) and acceptable in CLI (AUC 0.736, sensitivity 0.63, specificity 0.72). An optimal VQ-6 threshold for a substantial clinical benefit was determined at 3.5 scale steps among IC patients and 4.5 in CLI patients. Conclusions: The suggested thresholds for minimum important difference and substantial clinical benefit could be used when evaluating VQ-6 outcomes following different interventions in PAD and in the design of clinical trials.